UKHTI VS UGHTEA: ARABIC KINSHIP ADDRESS TERM AS SLANG AND IDENTITY IN INDONESIAN TWITTER - Qonitah, Salma; Triwinarti, Wiwin (International Review of Humanities Studies, 2020)
Microblogging has taken a quotidian position in the scope of internet usage. This research explores the pragmatic of ughtea, a slang form of ukhti, as a term of address slang and identity in Twitter’s prominent behaviour on virtual sphere: tweeting. Semantically, ukhti refers to “sister” of a possessive pronoun of the first person i.e. the speaker, both in biological and ideological contexts. For the last two years (2018—2019), the usage of the term ukhti has undergone the extension of its meaning through its use among Indonesian Twitter users by changing its form into ughtea as a slang with degenerative meaning, in order to insinuate the exclusivity of the use of the term ukhti among Indonesian conservative Muslims and the misbehavior of ukhti. As a result, the meaning of the term ukhti experiences pejoration. These certain Indonesian Twitter users, according to McCulloch’s classification of Internet People (2019) are classified as Post Internet People. This research problem focuses on the analysis of the speakers, terms, and how both terms used in the context of pejoration. This study aims to analyze both terms in terms of shifting meaning in terms of speakers, speech, and usage by implementing corpus linguistic approach and Martin and White (2005)’s appraisal system. Data sources were obtained from Twitter users' tweets during a certain period (October 2019).